The Impact of Paternal Support on Maternal Perception During Pregnancy - Rina K Kusumaratna; Saekhol Bakri; Raditya Nuraffi Kusumaputera (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2026)
Paternal involvement in maternal health is a critical yet often underexplored factor in enhancing antenatal care (ANC) attendance and pregnancy outcomes. This study aimed to examine how paternal support—across emotional, instrumental, informational, and appraisal dimensions—shapes maternal perception during pregnancy and influences ANC attendance. A quantitative, cross-sectional study was conducted among 38 couples of pregnant women attending Poncol Primary Health Center in Semarang, Central Java, Indonesia. Using the FSDP’s structured questionnaire, the study assessed four dimensions of paternal support. Findings revealed that father involvement varied across support types, with higher levels of emotional and instrumental support positively associated with ANC attendance. Moreover, the consistency of perceived support significantly influenced maternal perception. In conclusion, maternal perception of paternal support is closely linked to ANC-seeking behavior and the overall pregnancy experience. Enhancing father engagement through targeted, culturally responsive interventions may foster improved outcomes for both mothers and infants